Novel Quinolinonyl Diketo Acid Derivatives as HIV-1 Integrase Inhibitors: Design, Synthesis, and Biological Activities - Di Santo, Roberto (American Chemical Society, 2008)
[Image: see text] Novel quinolinonyl diketo acids were designed to obtain integrase (IN) inhibitors selectively active against the strand transfer (ST) step of the HIV integration process. Those new compounds are characterized by a single aryl diketo acid (DKA) chain in comparison to 4, a bifunctional diketo acid reported by our group as an anti-IN agent highly potent against both the 3′-processing and ST steps. Compound 6d was the most potent derivative in IN enzyme assays, while 6i showed the highest potency against HIV-1 in acutely infected cells. The selective inhibition of ST suggested the newly designed monofunctional DKAs bind the IN−DNA acceptor site without affecting the DNA donor site.